GHG or not GHG Accounting for diverse mitigation contributions in the post-2020 climate framework - Hood, Christina (OECD/IEA Climate Change Expert Group Papers, 2014)
It is likely that a diverse range of nationally-determined mitigation contributions will be communicated by Parties under the 2015 climate change agreement. An effective post-2020 accounting framework to understand and track implementation of these mitigation contributions will therefore need to accommodate a range of contribution types and varying national capacities. With Parties now undertaking domestic preparations for developing intended mitigation contributions for the 2015 agreement, three key issues are: (i) what up-front information should be provided alongside intended mitigation contributions to facilitate understanding of the intended contributions and their expected impacts on greenhouse gas (GHG) emissions levels; (ii) what accounting rules or guidance for post-2020 mitigation contributions (if any) would it be helpful to agree or develop before 2020, to facilitate understanding of intended contributions and their expected impacts on GHG emissions levels; and (iii) the timing of key decisions on accounting issues, taking into account the agreed timetable for communication of intended mitigation contributions. This paper explores these questions in greater detail and highlights issues that Parties may wish to consider when preparing and communicating their mitigation contributions. Providing Parties with some structure for the framing of intended mitigation contributions could help simplify domestic preparations for these intended contributions, in particular for those Parties with lower institutional capacity